A polyacid-based cobalt-containing magnetic compound
By synthesizing polyacid-based cobalt-containing magnetic compounds and adjusting their molecular spatial accumulation structure, the problem that the rotational change temperature of existing magnetic bistable materials is difficult to regulate to room temperature, and the rotational change temperature regulation of cobalt ions is realized, and the application of magnetic bistable materials in the fields of molecular switching and temperature sensing is promoted.
Patent Information
- Application Number
- CN202211516716.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-11-29
AI Technical Summary
The rotational change temperature of existing magnetic bistable materials is difficult to regulate to near room temperature, which limits its practical application in the fields of molecular switching, temperature sensing, etc.
By synthesizing polyacid-based cobalt-containing magnetic compounds, the molecular spatial accumulation structure of the compounds is adjusted by synthesis of polyacid-based cobalt ions by layered diffusion method and single-crystal X-ray diffraction technology to control the self-rotation change temperature of cobalt ions.
The rotational change temperature of cobalt ions was successfully regulated, so that it could achieve a transition between high-spin and low-spin states near room temperature, providing the feasibility of magnetic bistable materials in practical applications.
Smart Images

Figure CN115785167B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of polyacid-based magnetic materials, and specifically relates to a polyacid-based cobalt-containing magnetic compound, which realizes the regulation of the transition temperature between high-spin and low-spin states and is applied to the fields of molecular switches and temperature sensors. Background Art
[0002] Magnetic bistable molecules generally have two stable or metastable electronic configurations. They are molecular-based materials with great application potential and belong to the frontier research direction of science and technology. They have important scientific value in the development of molecular switches, temperature sensors and information storage devices. 4 -3d 7 When transition metal ions are in a suitable coordination field, their electronic spin states can be reversibly transformed between high-spin states and low-spin states under the stimulation of external conditions. In different spin states, the color, shape, conductivity and magnetic properties of such materials will change significantly. In order to realize the practical application of such materials, it is necessary to regulate their transition temperature to near room temperature. At present, researchers use photoinduction, ligand modification, solvent effect and guest molecule effect to regulate the transition temperature of materials. In 2018, the applicant systematically studied the effect of different solvent molecules on the transition temperature of the compound [Fe(tpa)(NCSe)2]. The results showed that the intermolecular force between protic solvents (water, methanol and ethanol) and the molecular framework is strong, which is conducive to stabilizing low-spin divalent iron ions, resulting in a higher spin transition temperature, while aprotic solvents (dichloromethane) exhibit a lower spin transition temperature (Cryst. Growth Des. 2018, 18, 6853-6862). In 2019, the applicants reported the magnetic properties and spin transition temperatures of three one-dimensional coordination polymers under different ligand field strengths by adjusting the ligand field strength of the axial anion, and studied the photoexcited spin state capture behavior of the material by lasers of a specific wavelength (Dalton Trans., 2019, 48, 9243–9249). This shows that synthesizing new molecular structures and clarifying the intrinsic connection between structure and performance through structural analysis are effective means to regulate the spin transition temperature of magnetic bistable materials. Summary of the invention
[0003] The invention provides a polyacid-based cobalt-containing magnetic compound to achieve effective regulation of the spin transition temperature of a magnetic bistable material, thereby laying a foundation for preparing a magnetic material that transitions near room temperature and realizing its practical application.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] A polyacid-based cobalt-containing magnetic compound, the molecular formula of which is [Co(C 20H 14 N4)2]2(Mo8O 26 )·Solv, during preparation, ammonium heptamolybdate is dissolved in distilled water, the pH of the solution is adjusted and then placed at the bottom of a test tube; a mixed solution of distilled water and acetonitrile is added as a transition layer, and the upper layer is a solution containing cobalt chloride and 4'-(4-pyridyl)-2,2':6',2"-terpyridine; the solution is allowed to stand and diffuse slowly to obtain red block crystals, i.e., a polyacid-containing cobalt magnetic compound; the pH value of the ammonium heptamolybdate solution is adjusted to 4.1, and the volume ratio of distilled water and acetonitrile in the transition layer is 1:1.
[0006] A polyacid-based cobalt-containing magnetic compound, the molecular formula of which is [Co(C 20 H 14 N4)2]2(Mo8O 26 )·Solv, during preparation, ammonium heptamolybdate is dissolved in distilled water, the pH of the solution is adjusted and then placed at the bottom of a test tube; a mixed solution of distilled water and acetonitrile is added as a transition layer, and the upper layer is a solution containing cobalt chloride and 4'-(4-pyridyl)-2,2':6',2"-terpyridine; the solution is allowed to stand and diffuse slowly to obtain red block crystals, i.e., a polyacid-containing cobalt magnetic compound; the pH value of the ammonium heptamolybdate solution is adjusted to 4.3, and the volume ratio of distilled water and acetonitrile in the transition layer is 1:1.
[0007] A polyacid-based cobalt-containing magnetic compound, the molecular formula of which is [Co(C 20 H 14 N4)2]2(Mo8O 26 )·Solv, during preparation, ammonium dimolybdate is dissolved in acetic acid-sodium acetate buffer solution, the pH of the solution is adjusted and then placed at the bottom of a test tube; a mixed solution of distilled water and acetonitrile is added as a transition layer, and the upper layer is a solution containing cobalt chloride and 4'-(4-pyridyl)-2,2':6',2"-terpyridine; the solution is allowed to stand and diffuse slowly to obtain red block crystals, i.e., a polyacid-containing cobalt magnetic compound; the pH value of the ammonium dimolybdate solution is adjusted to 4.8, and the volume ratio of distilled water and acetonitrile in the transition layer is 1:1.
[0008] The spin transition temperature of polyacid-based cobalt-containing magnetic compounds is 353K.
[0009] The spin transition temperature of polyacid-based cobalt-containing magnetic compounds is 342K.
[0010] The spin transition temperature of polyacid-based cobalt-containing magnetic compounds is 322K.
[0011] The present invention provides the above three examples of polyacid-based cobalt-containing magnetic compounds. Studies have found that the chemical compositions of the three compounds are similar, but their molecular spatial stacking structures are significantly different. Based on this, there are great differences in the intermolecular interactions among the three, resulting in their spin transition temperatures of 353K, 342K and 322K, respectively. Therefore, under the same ligand field strength conditions, the spin transition temperature of the magnetic material can be regulated by changing the crystal form of the compound.
[0012] The polyacid-based cobalt-containing magnetic compound of the present invention is synthesized by a layered diffusion method, using a molybdate solution as a lower layer, a magnetic center cobalt ion and an organic ligand as an upper layer, and a mixed solvent as an intermediate layer to obtain a single crystal sample of the compound. Compared with composite magnetic materials, the present invention has the following advantages:
[0013] 1) The present invention uses single crystal X-ray diffraction technology to accurately determine the molecular structures of three compounds;
[0014] 2) The present invention adopts a layered diffusion method to synthesize the product, and the reaction is carried out at room temperature and pressure, so the experimental operation is safe and environmentally friendly;
[0015] 3) The present invention explores the effect of the molecular spatial stacking structure on the spin transition temperature of cobalt ions by controlling the ligand field strength;
[0016] 4) The present invention effectively regulates the spin transition temperature of cobalt ions, providing an experimental basis and theoretical reference for obtaining a magnetic bistable material that transitions near room temperature;
[0017] 5) Compared with composite magnetic materials, the mechanistic relationship between the structure and transition temperature of the polyacid-based cobalt-containing magnetic compound of the present invention is clearer. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is the molecular stacking structure of the polyacid-based cobalt-containing magnetic compound with a spin transition temperature of 353K;
[0019] Figure 2 It is the molecular stacking structure of the polyacid-based cobalt-containing magnetic compound with a spin transition temperature of 342K;
[0020] Figure 3 It is the molecular stacking structure of the polyacid-based cobalt-containing magnetic compound with a spin transition temperature of 322K;
[0021] Figure 4 The spin transition temperature of the polyoxometalate cobalt-containing magnetic compound is 353K. M TT and d(χ M T) / dT-T curve;
[0022] Figure 5The spin transition temperature of the polyoxometalate cobalt-containing magnetic compound is 342K. M TT and d(χ M T) / dT-T curve;
[0023] Figure 6 The spin transition temperature of the polyoxometalate-containing cobalt magnetic compound is 322K. M TT and d(χ M T) / dT-T curve; DETAILED DESCRIPTION
[0024] like Figure 1 , 2 , 3, 4, 5, 6, a polyacid-based cobalt-containing magnetic compound, the molecular formula of which is [Co(C 20 H 14 N4)2]2(Mo8O 26 )·Solv, during the preparation, ammonium heptamolybdate is dissolved in distilled water, the pH of the solution is adjusted and then placed at the bottom of a test tube; a mixed solution of distilled water and acetonitrile is added as a transition layer, and the upper layer is a solution of cobalt chloride and 4'-(4-pyridyl)-2,2':6',2"-terpyridine; the solution is allowed to stand and diffuse slowly to obtain red block crystals, which are polyacid-containing cobalt magnetic compounds; the pH value of the ammonium heptamolybdate solution is adjusted to 4.1, and the volume ratio of distilled water and acetonitrile in the transition layer is 1:1. The spin transition temperature of the polyacid-containing cobalt magnetic compound is 353K.
[0025] A polyacid-based cobalt-containing magnetic compound, the molecular formula of which is [Co(C 20 H 14 N4)2]2(Mo8O 26 )·Solv, during preparation, ammonium heptamolybdate is dissolved in distilled water, the pH of the solution is adjusted and then placed at the bottom of a test tube; a mixed solution of distilled water and acetonitrile is added as a transition layer, and the upper layer is a solution containing cobalt chloride and 4'-(4-pyridyl)-2,2':6',2"-terpyridine; the solution is allowed to stand and diffuse slowly to obtain red block crystals, which are polyacid-containing cobalt magnetic compounds; the pH value of the ammonium heptamolybdate solution is adjusted to 4.3, and the volume ratio of distilled water and acetonitrile in the transition layer is 1:1. The spin transition temperature of the polyacid-containing cobalt magnetic compound is 342K.
[0026] A polyacid-based cobalt-containing magnetic compound, the molecular formula of which is [Co(C 20 H 14 N4)2]2(Mo8O 26)·Solv, during preparation, ammonium dimolybdate is dissolved in acetic acid-sodium acetate buffer solution, the pH of the solution is adjusted and then placed at the bottom of a test tube; a mixed solution of distilled water and acetonitrile is added as a transition layer, and the upper layer is a solution containing cobalt chloride and 4'-(4-pyridyl)-2,2':6',2"-terpyridine; the solution is allowed to stand and diffuse slowly to obtain red block crystals, which are polyacid-containing cobalt magnetic compounds; the pH value of the ammonium dimolybdate solution is adjusted to 4.8, and the volume ratio of distilled water and acetonitrile in the transition layer is 1:1. The spin transition temperature of the polyacid-containing cobalt magnetic compound is 322K.
[0027] Example 1: A polyacid-based cobalt-containing magnetic compound having the molecular formula [Co(C 20 H 14 N4)2]2(Mo8O 26 )·Solv, when prepared,
[0028] 1) Dissolve 0.528 g of ammonium heptamolybdate in 50 mL of distilled water, and adjust the pH value to 4.1 with glacial acetic acid and sodium hydroxide to obtain solution A.
[0029] 2) A 15 mL acetonitrile solution containing 0.05 g of 4'-(4-pyridyl)-2,2':6',2"-terpyridine was mixed with a 5 mL aqueous solution containing 0.08 g of cobalt chloride hexahydrate to obtain a solution B.
[0030] 3) 5 mL of solution A was measured as the lower layer, 5 mL of solution B was measured as the upper layer, and 5 mL of a mixed solution of distilled water and acetonitrile was measured as the middle layer. Compound 1 was obtained by slow diffusion.
[0031] Example 2: A polyacid-based cobalt-containing magnetic compound having the molecular formula [Co(C 20 H 14 N4)2]2(Mo8O 26 )·Solv, when prepared,
[0032] 1) Dissolve 1.2 g of ammonium heptamolybdate in 100 mL of distilled water, add 20 mL of glacial acetic acid, and adjust the pH value to 4.3 with sodium hydroxide to obtain solution A.
[0033] 2) A 60 mL acetonitrile solution containing 0.09 g of 4'-(4-pyridyl)-2,2':6',2"-terpyridine was mixed with a 20 mL aqueous solution containing 0.1 g of cobalt chloride hexahydrate to obtain a solution B.
[0034] 3) 5 mL of solution A was measured as the lower layer, 5 mL of solution B was measured as the upper layer, and the middle layer was 5 mL of a mixed solution of distilled water and acetonitrile. Compound 2 was obtained by slow diffusion.
[0035] Example 3: A polyacid-based cobalt-containing magnetic compound having the molecular formula [Co(C 20 H 14 N4)2]2(Mo8O 26 )·Solv, during preparation, 1) dissolve 0.1 g of ammonium dimolybdate in 10 mL of acetic acid-sodium acetate buffer solution, and adjust its pH value to 4.8 with glacial acetic acid and sodium hydroxide to obtain solution A.
[0036] 2) A 60 mL acetonitrile solution containing 0.05 g of 4'-(4-pyridyl)-2,2':6',2"-terpyridine was mixed with a 20 mL aqueous solution containing 0.05 g of cobalt chloride hexahydrate to obtain a solution B.
[0037] 3) 5 mL of solution A was measured as the lower layer, 5 mL of solution B was measured as the upper layer, and the middle layer was 5 mL of a mixed solution of distilled water and acetonitrile. Compound 3 was obtained by slow diffusion.
[0038] Embodiment 4:
[0039] Single crystal samples of the compounds of the three embodiments were collected respectively, and the temperature-dependent magnetic susceptibility test was performed. The spin transition temperature of the cobalt ion in the compound of Example 1 was 353K, the spin transition temperature of the cobalt ion in the compound of Example 2 was 342K, and the spin transition temperature of the cobalt ion in the compound of Example 3 was 322K. This shows that the transition temperature of the cobalt ion between the high spin state and the low spin state is effectively adjusted by adjusting the molecular spatial stacking structure of the compound.
[0040] The present invention uses single crystal X-ray diffraction technology to determine the single crystal structures of the compound prepared in Example 1, the compound prepared in Example 2, and the compound prepared in Example 3.
[0041] The unit cell parameters of the compound prepared in Example 1 are as follows: triclinic system, Space group, unit cell parameters b=14.9219(6), α=110.385(2), β=99.744(2), γ=103.346(1), Z=2, R1=0.0431, wR2=0.1060.
[0042] The unit cell parameters of the compound prepared in Example 2 are as follows: triclinic system, Space group, unit cell parameters b=17.135(10), α=83.854(18), β=83.29(2), γ=71.338(16), Z=2, R1=0.0457, wR2=0.1123.
[0043] The unit cell parameters of the compound prepared in Example 3 are as follows: triclinic system, Space group, unit cell parameters b=16.5107(11), α=88.059(2), β=85.958(2), γ=72.060(2), Z=1, R1=0.0765, wR2=0.2270.
[0044] Figure 1 is the molecular stacking structure of the compound prepared in Example 1. Figure 1 It can be seen that the molecular layers formed by cations and anions in the compound prepared in Example 1 present an alternating arrangement pattern, and the arrangement of anions in each layer is exactly the same.
[0045] Figure 2 is the molecular stacking structure of the compound prepared in Example 2. Figure 2 It can be seen that the molecular layers formed by cations and anions in the compound prepared in Example 2 present an alternating arrangement pattern, but the directions of the anions in two adjacent layers are different.
[0046] Figure 3 is the molecular stacking structure of the compound prepared in Example 3. Figure 3 It can be seen that the cations and anions in the compound prepared in Example 1 do not form molecular layers separately, but appear alternately in the same layer. 26 ] 4- The anion layers are arranged alternately.
[0047] Figure 4 is the x of the compound prepared in Example 1 M TT and d(χ M T) / dT-T curve. Figure 4 It can be seen that the compound prepared in Example 1 has a temperature range of 10-200K. M T value is stable at 1.1cm 3 K mol -1 , corresponding to two low-spin divalent cobalt ions. As the temperature continues to rise, χ M T value increases slowly. When the temperature rises to 325K, χ M The T value increases rapidly, proving that the compound prepared in Example 1 exhibits thermally induced spin transition behavior. M T) / dT-T curve shows that the spin transition temperature of cobalt ion is 353K.
[0048] Figure 5 is the χ of compound 2 M TT and d(χ M T) / dT-T curve. Figure 5 It can be seen that the compound prepared in Example 2 has a temperature range of 10-200K. M T value is stable at 0.9cm 3 Kmol -1 When the temperature continues to rise, χ M T value increases slowly. When the temperature rises to 320K, χ M The T value increases rapidly, proving that the compound prepared in Example 2 exhibits thermally induced spin transition behavior. M From the T) / dT-T curve, we can see that the spin transition temperature of cobalt ion is 342K.
[0049] Figure 6 is the x of the compound prepared in Example 3 M TT and d(χ M T) / dT-T curve. Figure 6 It can be seen that the compound prepared in Example 3 has a temperature range of 10-200K. M T value is stable at 1.0cm 3 K mol -1 When the temperature continues to rise, χ M When the temperature rises to 300K, the T value increases slowly. M The T value increases rapidly, proving that the compound prepared in Example 3 exhibits thermally induced spin transition behavior. M From the T) / dT-T curve, we can see that the spin transition temperature of cobalt ion is 322K.
[0050] The present invention utilizes the crystal isomerism phenomenon under the same ligand field to explore the influence of the molecular spatial stacking structure on the high-spin and low-spin states of cobalt ions, realizes the regulation of the spin transition temperature of divalent cobalt ions, and provides an effective strategy for the development of spin-crossover materials that transition near room temperature.
[0051] The above-described embodiments of the present invention are intended to be illustrative and not restrictive, and the scope of the present invention is defined by the appended claims rather than the above description.
Claims
1. A polyacid-based cobalt-containing magnetic compound, characterized in that: Its molecular formula is [Co(C 20 H 14 N4)2]2(Mo8O 26 ) Solv During the preparation, ammonium heptamolybdate is dissolved in distilled water, and the pH of the solution is adjusted and then placed at the bottom of a test tube; a mixed solution of distilled water and acetonitrile is added as a transition layer, and the upper layer is a solution containing cobalt chloride and 4'-(4-pyridyl)-2,2':6',2''-terpyridine; the solution is allowed to stand and diffuse slowly to obtain red block crystals, namely, a polyacid-containing cobalt magnetic compound; the pH value of the ammonium heptamolybdate solution is adjusted to 4.1, and the volume ratio of distilled water and acetonitrile in the transition layer is 1:1; the spin transition temperature of the polyacid-containing cobalt magnetic compound is 353 K.
2. A polyacid-based cobalt-containing magnetic compound, characterized in that: Its molecular formula is [Co(C 20 H 14 N4)2]2(Mo8O 26 ) Solv, During the preparation, ammonium heptamolybdate is dissolved in distilled water, and the pH of the solution is adjusted and then placed at the bottom of a test tube; a mixed solution of distilled water and acetonitrile is added as a transition layer, and the upper layer is a solution containing cobalt chloride and 4'-(4-pyridyl)-2,2':6',2''-terpyridine; the solution is allowed to stand and diffuse slowly to obtain red block crystals, namely, a polyacid-containing cobalt magnetic compound; the pH value of the ammonium heptamolybdate solution is adjusted to 4.3, and the volume ratio of distilled water and acetonitrile in the transition layer is 1:1; the spin transition temperature of the polyacid-containing cobalt magnetic compound is 342 K.
3. A polyacid-based cobalt-containing magnetic compound, characterized in that: Its molecular formula is [Co(C 20 H 14 N4)2]2(Mo8O 26 ) Solv During the preparation, ammonium dimolybdate is dissolved in an acetic acid-sodium acetate buffer solution, and the pH of the solution is adjusted and then placed at the bottom of a test tube; a mixed solution of distilled water and acetonitrile is added as a transition layer, and the upper layer is a solution containing cobalt chloride and 4'-(4-pyridyl)-2,2':6',2''-terpyridine; the solution is allowed to stand and diffuse slowly to obtain red block crystals, namely, a polyacid-containing cobalt magnetic compound; the pH value of the ammonium dimolybdate solution is adjusted to 4.8, and the volume ratio of distilled water and acetonitrile in the transition layer is 1:1; the spin transition temperature of the polyacid-containing cobalt magnetic compound is 322 K.
Citation Information
Patent Citations
Structure and preparation method of cobalt-bridged flexible ligand and polymolybdate hybridized material
CN104086605A